Local convergence of exact and inexact newton’s methods for subanalytic variational inclusions - Cabuzel, Catherine (2015)
This paper deals with the study of an iterative method for solving a variational inclusion of the form 0 ∈ f (x)+F(x) where f is a locally Lipschitz subanalytic function and F is a set-valued map from Rn to the closed subsets of Rn. To this inclusion, we firstly associate a Newton then secondly an Inexact Newton type sequence and with some semistability and hemistability properties of the solution x∗ of the previous inclusion, we prove the existence of a sequence which is locally superlinearly convergent.